2004
DOI: 10.1089/089426804322994406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Facemask Leak on Aerosol Delivery from a pMDI-Spacer System

Abstract: The objective of this investigation was to study the relation between size and position of a mask leak on spacer output and lung dose. An upper-airway model (SAINT model, Erasmus MC) was connected to a breathing simulator. Facemasks with leaks ranging between 0 and 1.5 cm(2) were examined. Leaks were located close to the nose or close to the chin. During simulated breathing, 200 microg budesonide (Pulmicort, AstraZeneca) was delivered to the model via NebuChamber (AstraZeneca) with facemask. Spacer output and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 11 publications
0
48
0
2
Order By: Relevance
“…Crying and lack of proper mask seal are known to decrease intrapulmonary deposition. 17,18,20 An in vivo study by Esposito-Festen et al 21 demonstrated lack of acceptability and efficiency of aerosol delivery during sleep in a group of toddlers. This study highlighted the importance of interface acceptance to achieve good drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Crying and lack of proper mask seal are known to decrease intrapulmonary deposition. 17,18,20 An in vivo study by Esposito-Festen et al 21 demonstrated lack of acceptability and efficiency of aerosol delivery during sleep in a group of toddlers. This study highlighted the importance of interface acceptance to achieve good drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The patient inhales the aerosol while tidal breathing from a reservoir through a mouthpiece or face mask. For children, a good face mask design is important to maximise efficiency [39,40]. A child old enough to inhale through a mouthpiece should do so, as the efficiency of aerosol delivery can be doubled relative to inhalation by face mask [41].…”
Section: Wet Nebulisers: the Basicsmentioning
confidence: 99%
“…Even small leaks of 0.5 cm around the face mask decrease drug inhaled by children and infants by more than 50%. [30][31][32][33][34] Delivery of aerosolized medications in a blow-by fashion is commonly used for crying babies or uncooperative children, where the nebulization port of a nebulizer is directed toward the patient's face. Studies have documented blow-by medication administration is less efficient, compared with a face mask, as aerosol drug deposition decreases significantly with distance, and this use should be discouraged.…”
Section: Other Nuances and Characteristics Of Svnsmentioning
confidence: 99%
“…Studies have documented blow-by medication administration is less efficient, compared with a face mask, as aerosol drug deposition decreases significantly with distance, and this use should be discouraged. 30,[34][35][36] In summary, while the domain of SVNs can be highly variable, based on the nuances and characteristics described previously, the entire category has some common advantages and disadvantages, which are listed in Table 6.…”
Section: Other Nuances and Characteristics Of Svnsmentioning
confidence: 99%